Personality assessment through projetive movie pictures - "Dass, S.L" (New Delhi, 1974)
Prediction of personality is the central problem of psychology. Personality is one of those few subjects which have received special attention from psychologists in the post war period. It has been artly said that a human being does not have a personality; he is a personality. In this book Dr. Dass has made certain suggestions with respect to the conceptual basis of future movie pictures' tests. Developed on those line a test is likely to become a more effective tool of personality assessment. In the meantime it can be said that his work is a definite contribution to the projective techniques.
Keywords: Psychology